GEREJA DAN DIALOG BUDAYA BERCERMIN PADA MISI PAULUS - Stanislaus, Eko Riyadi (Jurnal Orientasi Baru, 2016)
A major topic in the relation between the church and culture is the capacity of the church to incarnate the core of its faith into the life of the local culture. The faith in God is expressed in various human expressions either cultic or cultural. The church doesnâ€™t risk its faith in God but expresses this faith in various ways adapted to the local culture where the church lives. Paul and his friends took effort to enter through the door of the Jews and the Greeks to bring the Gospel to them. Although he did not always get great success, his works have been producing great result. In the reflection ofÂ  the Asian Church regarding its existence in the life of Asia, the way to evangelization is, therefore, the incarnation of the Gospel in the life of the local culture.